COMPARISON BETWEEN THREE PENETROMETERS IN THE EVALUATION OF THE SOIL PENETRATION MECHANICAL RESISTANCE OF A RED EUTROFERRIC LATOSOL - Baesso, M. M.; Menezes, T. A. V.; Modolo, A. J.; Rosa, R. G.; Zuin, L. F. S. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Soil compaction triggers environmental and agronomic problems such as erosion, leaching and low productivity. The penetrometer is the instrument that measures the resistance of the introduction of a conical tipped rod into the ground; theoretically, more compacted soils offer greater resistance. There are a variety of penetrometer models in the market and literature: bench or field, manual or automatic, static (penetrograph) or dynamic (impact), with or without electronic data record etc. Of course, the question arises whether it is possible to compare data from different penetrometers. In the present work, we compared the field sensors (manual dynamic, manual static and automatic static). The experiment was carried out in a red eutroferric latosol (USDA oxisol) of clay, sandy clay and sandy clay loam textures in Pirassununga-SP, Brazil. The mechanical strength was evaluated simultaneously by the three penetrometers in eight soil layers between 0 e 0,40 m. The resistance varied inversely with soil moisture in the three penetrometers, It was concluded that it is safe to compare resistance values ​​from different penetrometers provided they have been collected under the same soil moisture condition.